Kontekstualisasi Teori Keadilan John Rawls Pada Konstelasi Kemasyarakatan di Indonesia - Syukron Wahyudhi; Faza Achsan Baihaqi (LPPM Institut Pesantren KH. Abdul Chalim, 2023)
Next year Indonesia held a political election. Political actors may express their aspirations and hope within the public sphere. As consequence, political contestation increases dramatically. While the expression is abundant, it can be called the democratic feast. But previous democratic feasts taught us that the process of electoral politics seems so far from its idealized norms. For example, the relationship between minority and majority has worsened because of identity politics. Why this is happening? This article wants to address that problem from Rawlsian point of view. Equipped with a theory of justice, we would reflect the condition of Indonesia’s political world. To consider the effect of strong religious attainment and religious plurality, our analysis will be complemented with a doctrinal perspective, especially from Quran and Bible. We found that, within modern-state politics, majoritarian power is allowed because it is the best way to ensure regulation bills pass smoothly. It is consistent with Rawls’ argument that majoritarian power flourishes within rational calculation about the goals of principles of justice. It is not quite different from doctrinal perspectives which insist on citizen participation as an essential part of national building.